POST-COLD WAR RUSSIAN NEIGHBOURHOOD POLICY UNTIL 2018 (Conference Zone, 2022)
This article outlines the main course of action in Russian foreign policy following the collapse of the Soviet Union in 1991. The article especially focuses on post-Soviet countries and bilateral relations with Russia, applying realist and liberal analyses of Russian struggle for regional hegemony.